Análogos experimentais de metacontingências: o efeito da retirada da conseqüência individual - Brocal, Andréa Lopez (2010)
The inclusion of the so-called cultural phenomenon as the object of interest or study of behavior analysis begins when Skinner describes human behavior and aspects which are characteristics of social relations. Other researchers in the behavior analysis interested in these studies, present in their studies (researches) the concept of metacontingency as a conceptual tool to the comprehension of cultural phenomenon. A number of attempts to produce analogous of metacontingency in an experimental environment have been made, and proceeding with these efforts the question which is the aim of the present study is whether the suspension of the consequences which are individually relevant, despite not having effects on the interlocking, would also have an effect on the selection of / by metacontingency. In other words, what would happen to the selected interlocking, if there was a suspension of contingencies to the operant behavior after the selection of / by metacontingencies? In order to do that, two experiments were designed. Experiment 1 was conducted by 3 (three) phases and the principal manipulation was removed from the individual consequence after the metacontingency was selected. The second experiment or Controlling Experiment, which did not include the selection phase and the strengthening of the operant behavior, in which only a determined relation between the participants and their consequent aggregated product were sequenced. The results indicated that in Experiment 1 there was not the simultaneous maintenance of the individual and cultural consequence. Nonetheless, it can be stated that both of them, at their own pace, showed to be under control of the programmed consequence. The Experiment 2 shows that independently of the selection of a specific operant behavior there was the selection of the IBCs and their aggregate product by cultural consequences. Results indicate that, despite of the operating selection being programmed, the aggregated product may emerge and the programmed cultural consequence may occur on the coordination as a way to strengthen it. Due to some circumstances which have arisen in Experiment 1, it is suggested that its replication with some modifications to determine the effects of the suspension of differential consequences of contingencies operating on IBCs